2019
DOI: 10.1111/acem.13850
|View full text |Cite
|
Sign up to set email alerts
|

Does Shared Decision Making Actually Occur in the Emergency Department? Looking at It from the Patients’ Perspective

Abstract: Objective: We sought to assess the frequency, content, and quality of shared decision making (SDM) in the emergency department (ED), from patients' perspectives.Methods: Utilizing a cross-sectional, multisite approach, we administered an instrument, consisting of two validated SDM assessment tools-the CollaboRATE and the SDM-Q-9-and one newly developed tool to a sample of ED patients. Our primary outcome was the occurrence of SDM in the clinical encounter, as defined by participants giving "top-box" scores on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Our findings provided contextual understandings of the perspectives of consumers and health professionals. The findings are consistent with the literature highlighting that collaboration and shared decision‐making between consumers and health professionals contribute to benefits in the management of consumer care (Schoenfeld et al, 2019; Wright et al, 2018). This collaboration is generally established within a context of personal and professional perceptions and understandings as consumers and health professionals work together to plan and attain shared goals (Allen et al, 2019; Born et al, 2017; Embrett & Randall, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings provided contextual understandings of the perspectives of consumers and health professionals. The findings are consistent with the literature highlighting that collaboration and shared decision‐making between consumers and health professionals contribute to benefits in the management of consumer care (Schoenfeld et al, 2019; Wright et al, 2018). This collaboration is generally established within a context of personal and professional perceptions and understandings as consumers and health professionals work together to plan and attain shared goals (Allen et al, 2019; Born et al, 2017; Embrett & Randall, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…In these situations, health professionals may simply adopt the path of least resistance and give way to consumer expectations (Ives et al, 2018; Keijzers et al, 2018). Hence, to effectively engage in a shared decision‐making process, health professionals need to feel supported (Schoenfeld et al, 2019). Finding a balance focused on consumer‐centered care among consumers, caregivers, and health professionals is imperative (Ives et al, 2018; Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Implementing SDM in clinical practice has been associated with improved patients' selfreported outcomes and their understanding of risks, as well as greater satisfaction with the consultation process [6][7][8]. In addition, SDM improves quality of care and patient adherence to medication, and consequently contributes to the optimization of health costs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Reports about SDM, ACP, and code status in the COVID-19 context are scarce. The process of SDM has been studied earlier in a general ER environment and showed a 49% compliance rate using a composite instrument [ 15 ]. Other research has shown that there was no difference in frequency of code status documentation in COVID-19 patients opposed to the pre-COVID cohort [ 16 ].…”
Section: Discussionmentioning
confidence: 99%